Students’ Acceptance of Technology Use in Learning English Pharmacy - Vivit Rosmayanti; Nurdin Noni; Andi Anto Patak (Universitas Negeri Makassar, 2022)
This study aims at determining how Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions influenced Behavioral intentions to use technology in learning English Pharmacy. This study employed a sample of 100 pharmacy students who were enrolled in an English pharmacy course. The samples were chosen using the quota sampling technique. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was performed to measure students' acceptance of the use of technology in this study. The findings of this study indicated that the four aspects mentioned above, such as Performance Expectations, Effort Expectations, Social Influences, and Facilitation Conditions, have a favorable impact on students' Behavioral intentions when using technology to learn English Pharmacy. However, only 40% of the four factors could explain the influence on Behavioral intention. The impact of this study is that it can lead the way and serve as a reference for future research on the UTAUT approach in a larger scope. In addition, the university should be able to increase the benefits and usability of technology as a learning resource by developing its own Learning Management System (LMS), which is easy to use.